Key climate change stressors of marine ecosystems along the path of the East African coastal current. (1st July 2021) - Jacobs, Z.L.; Yool, A.; Jebri, F.; Srokosz, M.; van Gennip, S.; Kelly, S.J.; Roberts, M.; Sauer, W.; Queirós, A.M.; Osuka, K.E.; Samoilys, M.; Becker, A.E.; et al.
Abstract: For the countries bordering the tropical Western Indian Ocean (TWIO), living marine resources are vital for food security. However, this region has largely escaped the attention of studies investigating potential impacts of future climate change on the marine environment . Understanding how marine ecosystems in coastal East Africa may respond to various climatic stressors is vital for the development of conservation and other ocean management policies that can help to adapt to climate change impacts on natural and associated human systems. Here, we use a high-resolution (1/4°) ocean model, run under a high emission scenario (RCP 8.5) until the end of the 21st century, to identify key regionally important climate change stressors over the East African Coastal Current (EACC) that flows along the coasts of Kenya and Tanzania. We also discuss these stressors in the context of projections from lower resolution CMIP5 models. Our results indicate that the main drivers of dynamics and the associated ecosystem response in the TWIO are different between the two monsoon seasons . Our high resolution model projects weakening of the Northeast monsoon (December–February) winds and slight strengthening of the Southeast monsoon (May–September) winds throughout the course of the 21st century, consistent with CMIP5 models. The projected shallower mixed layers and weaker upwelling during the Northeast Monsoon considerably reduce the availability of surface nutrients and primary production. Meanwhile, primary production during the Southeast monsoon is projected to be relatively stable until the end of the century. In parallel, a widespread warming of up to 5 °C is projected year-round with extreme events such as marine heatwaves becoming more intense and prolonged, with the first year-long event projected to occur as early as the 2030s. This extreme warming will have significant consequences for both marine ecosystems and the coastal populations dependent on these marine resources. These region-specific stressors highlight the importance of dynamic ocean features such as the upwelling systems associated with key ocean currents. This indicates the need to develop and implement a regional system that monitors the anomalous behaviour of such regionally important features. Additionally, this study draws attention to the importance of investment in decadal prediction methods, including high resolution modelling, that can provide information at time and space scales that are more directly relevant to regional management and policy making. Graphical abstract: Image 1 Highlights: Widespread warming of up to 5 °C projected in the Western Indian Ocean by 2100. First year-long marine heatwaves projected as early as 2030 for the region. Decline in Western Indian Ocean productivity projected by CMIP5 models. Projected weakening of northeast monsoon winds leading to reduced productivity. Projected reduction in connectivity and nutrient supply to the East African coast.